Flow Chemistry Syntheses of Styrenes, Unsymmetrical Stilbenes and Branched Aldehydes. Issue 1 (20th December 2012) - Bourne, Samuel L.; O'Brien, Matthew; Kasinathan, Sivarajan; Koos, Peter; Tolstoy, Päivi; Hu, Dennis X.; Bates, Roderick W.; Martin, Benjamin; Schenkel, Berthold; Ley, Steven V.
Abstract Two tandem flow chemistry processes have been developed. A single palladium‐catalysed Heck reaction with ethylene gas provides an efficient synthesis for functionalised styrenes. Through further elaboration the catalyst becomes multi‐functional and performs a second Heck reaction providing a single continuous process for the synthesis of unsymmetrical stilbenes. In addition, the continuous, rhodium‐catalysed, hydroformylation of styrene derivatives with syngas affords branched aldehydes with good selectivity. Incorporation of an in‐line aqueous wash and liquid–liquid separation allowed for the ethylene Heck reaction to be telescoped into the hydroformylation step such that a single flow synthesis of branched aldehydes directly from aryl iodides was achieved. The tube‐in‐tube semi‐permeable membrane‐based gas reactor and liquid–liquid separator both play an essential role in enabling these telescoped flow processes.